Micropillar Compression of MoSi2 Single Crystals. Issue 1760 (13th January 2015) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Nakatsuka, Satoshi; Kishida, Kyosuke; Inui, Haruyuki
ABSTRACT Deformation behavior of MoSi2 has been studied by micropillar compressions of single crystalline specimens prepared by focused ion beam (FIB) technique as a function of crystal orientation at room temperature. Activation of the 011<100> and 01<alternatives> <![CDATA[3]]> </alternatives><331> slip systems were observed in the micropillars compressed along [<alternatives> <![CDATA[1]]> </alternatives>10] and [0 15 1], respectively. The CRSS values for each slip system exhibit an approximate power law relationship with the edge length of micropillar. The 01<alternatives> <![CDATA[3]]> </alternatives><331> slip exhibit much stronger size-dependence than the 011<100> slip system.